HUBUNGAN PARITAS DENGAN TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS TEGALREJO YOGYAKARTA - Bernados Ferry Dwi Nugroho; Widiastuti Widiastuti; Suswatiningsih Suswatiningsih (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2014)
ABSTRACT Background: Period end of the stage of pregnancy (third trimester) is a stressful time into labor. Increased physical distress and ineffective labor will cause anxiety and discomfort. There is a reality in the health center Tegalrejo that pregnant women feel different anxiety, anxiety in pregnancy can be affected by several factors including knowledge, education level, age, gender, psychological, spousal support, and the parity. Objective: To know the relationship of parity with the level of anxiety in pregnant women in the third trimester Tegalrejo Health Center Yogyakarta. Methods: The study design is an analytical survey with cross sectional approach. The respondents of this study were 30 third trimester pregnant women respondents. Accidental sampling method and data analysis with correlation formula Chi Square.Results: In the statistical analysis Chi Square (ρ = 0.938) there was no association between parity with the level of anxiety in Pregnancy Trimester III in Yogyakarta Tegalrejo health center, but still got anxiety in pregnant women either mild anxiety to severe anxiety. Conclusion: There was no association between parity with the level of anxiety in pregnant women in the third trimester Tegalrejo Health Center Yogyakarta